2007
DOI: 10.1590/s1806-83242007000100007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral hemangioma, vascular malformation and varix in a Brazilian population

Abstract: Hemangioma, vascular malformation and varix are benign vascular lesions, common in the head and neck regions. Studies about the prevalence of these lesions in the oral cavity are scarce. The aim of this study was to estimate the prevalence of and to obtain clinical data on oral hemangioma, vascular malformation and varix in a Brazilian population. Clinical data on those lesions were retrieved from the clinical forms from the files of the Oral Diagnosis Service, School of Dentistry, Federal University of Minas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
2
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 23 publications
5
64
2
16
Order By: Relevance
“…3 Most common site for epulis in present study was gingiva which is similar to Al Khateeb et al and Kadeh et al 3,9 In present study most common site for Haemangioma was lip but in study of Corrêa et al and Allon et al most common site was tongue. 22,23 In present study Hemangioma was exclusively seen in females but Allon et al found male female ratio M:F 1.3:1 and Corrêa et al found M:F 0.4:1. 22,23 In present study most common age group for haemangioma was 21-30 years age group which is comparable to Corrêa et al 22 In present study mean age for Squamous Papilloma was 46.6 years which is similar to Torres-Domingo et al study.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…3 Most common site for epulis in present study was gingiva which is similar to Al Khateeb et al and Kadeh et al 3,9 In present study most common site for Haemangioma was lip but in study of Corrêa et al and Allon et al most common site was tongue. 22,23 In present study Hemangioma was exclusively seen in females but Allon et al found male female ratio M:F 1.3:1 and Corrêa et al found M:F 0.4:1. 22,23 In present study most common age group for haemangioma was 21-30 years age group which is comparable to Corrêa et al 22 In present study mean age for Squamous Papilloma was 46.6 years which is similar to Torres-Domingo et al study.…”
Section: Discussioncontrasting
confidence: 41%
“…22,23 In present study Hemangioma was exclusively seen in females but Allon et al found male female ratio M:F 1.3:1 and Corrêa et al found M:F 0.4:1. 22,23 In present study most common age group for haemangioma was 21-30 years age group which is comparable to Corrêa et al 22 In present study mean age for Squamous Papilloma was 46.6 years which is similar to Torres-Domingo et al study. 24 Male to female ration in present study was M:F 0.66:1 but in Torres-Domingo et al study it was M:F 0.9:1 and in Al Khateeb et al it was M:F 1.3:1.…”
Section: Discussioncontrasting
confidence: 41%
“…3 Flap of mucosa and submucosa. It highlights major artery with thickened walls with stenotic lumen and numerous vessels around the wound and widespread extravasation (hematoxylin-eosin stain, original magnification 9100) arteriovenous malformation) that require support for further investigation [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian mengenai vascular malformation yang dilakukan pada salah satu universitas di Brazil selama 10 tahun (1992-2002) terhadap 2.419 kasus, didapati prevalensinya sebesar 1,3%. 7 Sedangkan hamartoma intraoral yang terdiri dari jenis jaringan lainnya sangat jarang ditemukan. Bila ditemui, kebanyakan kasus yang dilaporkan terdapat pada atau sekitar midline posterior lidah, palatum durum, dan gingiva.…”
Section: Pembahasanunclassified